2019
DOI: 10.1177/0022466919892955
|View full text |Cite
|
Sign up to set email alerts
|

Teaching High School Students With Disabilities to Advocate for Academic Accommodations

Abstract: One factor that may contribute to the success of students with disabilities in postsecondary educational settings may be their ability to advocate for academic accommodations. By incorporating self-determination practices into the curriculum and transition process during high school, students with disabilities may acquire the self-advocacy skills for postsecondary settings. The purpose of this study was to examine the effects of a modified Self-Advocacy and Conflict Resolution (mSACR) training program on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…It is critical for students to receive self-advocacy instruction as part of K-12 transition practices. Findings from this study can inform research into the use of instructional interventions to teach high school students with LD and with ADHD self-advocacy skills needed to request academic accommodations (e.g., Holzberg et al, 2019;Lopez et al, 2020). Students' communication with Professor Williams in this study reinforces the importance of components of self-advocacy as previously conceptualized by Test and colleagues (2005), such as the need for students to demonstrate knowledge of self (e.g., explaining their needs and how an accommodation addresses those needs) and knowledge of resources (e.g., institutional processes related to their accommodations).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is critical for students to receive self-advocacy instruction as part of K-12 transition practices. Findings from this study can inform research into the use of instructional interventions to teach high school students with LD and with ADHD self-advocacy skills needed to request academic accommodations (e.g., Holzberg et al, 2019;Lopez et al, 2020). Students' communication with Professor Williams in this study reinforces the importance of components of self-advocacy as previously conceptualized by Test and colleagues (2005), such as the need for students to demonstrate knowledge of self (e.g., explaining their needs and how an accommodation addresses those needs) and knowledge of resources (e.g., institutional processes related to their accommodations).…”
Section: Discussionmentioning
confidence: 95%
“…Participants were subsequently asked to generalize the skills by contacting their teachers to arrange a meeting to discuss accommodations. These studies have found a functional relationship between SACR instruction and the ability of students with LD and/or ADHD to request accommodations, either with a high school teacher (Lopez et al, 2020) or a college professor (Holzberg et al, 2019;Walker & Test, 2011) Given the evidence that students with LD and students with ADHD underutilize accommodations that could support positive outcomes, it is important to understand how these groups of students can be better prepared to access accommodations in postsecondary education. The purpose of the present study was to work backward to inform instruction to prepare high school students to advocate for accommodations by examining how current postsecondary students with LD and students with ADHD discuss accommodations with professors.…”
Section: Introductionmentioning
confidence: 99%
“…With an increasingly more diverse and inclusive postsecondary population, it is vital that professionals have a repertoire of interventions that are effective in teaching the skills needed to be successful in IPSE programs to individuals with IDD. Upon leaving high school, responsibilities for requesting accommodations and modifications shift from the school service personnel and family members to the individual with the disability (Lopez et al, 2020). Researchers need to determine effective ways to teach essential self-advocacy skills, such as requesting academic accommodations, that are frequently needed by consumers on a college campus.…”
Section: Discussionmentioning
confidence: 99%
“…When students with disabilities transition from high school to college they often lack the resourcefulness of their peers and may struggle to identify ways to problem-solve and self-advocate in the postsecondary setting (Lopez et al, 2020). Self-advocacy is defined as needs and wants and to make decisions about the supports needed to achieve them (Daly-Cano et al, 2015, p. 214).…”
Section: Requesting Accommodationsmentioning
confidence: 99%
See 1 more Smart Citation